Use of Web 2.0 technology tool – educational blog – in the system of foreign language teaching - Alona M. Prykhodko; Oksana O. Rezvan; Nataliia P. Volkova; Stanislav T. Tolmachev (CTE Workshop Proceedings, 2019)
This paper discusses the use of a Web 2.0 technology tool – educational blog – in the system of teaching foreign languages for enhancement of teaching effectiveness and optimization of students’ performance. The authors describe the content, characteristics and didactic properties of an educational blog as an alternative or auxiliary educational environment, define its methodological objectives and list a number of advantages of this approach versus conventional teaching model. The effectiveness of the above-mentioned Web 2.0 technology tool was confirmed by the experiment which showed that an educational blog integrated in a foreign language teaching system contributed to optimization of the process of teaching and learning, development of foreign language communicative competence of students and thereby allowed them to acquire not only communicative but also technological skills.